Peran Aparatur Kecamatan Medan Timur Kota Medan dalam Pembauatan E-KTP Pada Tahun 2019 - Elisabella, Elisabella; Kadir, Abdul; Lubis, Yurial Arief (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2024)
The creation of E-KTP has become an important step in improving online population administration services, to improve the effectiveness and efficiency of governance. However, in the process of public services, there are often obstacles that can hinder the smooth and effective running and effectiveness of these services. These constraints include technical problems such as software and hardware malfunctions, lack of requirements and data, and non-technical constraints such as time discipline and availability of tool facilities. To overcome these challenges, comprehensive efforts are needed, including periodic maintenance of software and hardware, socialization to the public regarding the requirements for applying for E-KTP, coordination between various related parties, and strategic measures such as infrastructure improvement and HR training.  This study aims to explore the role of the East Medan District Apparatus in making E-KTP, as well as provide recommendations to improve the performance and services of the Apparatus. By understanding and overcoming existing obstacles, it is hoped that population administration services, especially in making E-KTP, can be improved as a whole.